Graphene Hybrid Metasurfaces for Mid-Infrared Molecular Sensors - Yager, Tom; Chikvaidze, George; Wang, Qin; Fu, Ying (MDPI, 2023)
We integrated graphene with asymmetric metal metasurfaces and optimised the geometry dependent photoresponse towards optoelectronic molecular sensor devices. Through careful tuning and characterisation, combining finite-difference time-domain simulations, electron-beam lithography-based nanofabrication, and micro-Fourier transform infrared spectroscopy, we achieved precise control over the mid-infrared peak response wavelengths, transmittance, and reflectance. Our methods enabled simple, reproducible and targeted mid-infrared molecular sensing over a wide range of geometrical parameters. With ultimate minimization potential down to atomic thicknesses and a diverse range of complimentary nanomaterial combinations, we anticipate a high impact potential of these technologies for environmental monitoring, threat detection, and point of care diagnostics. © 2023 by the authors. --//-- Yager T., Chikvaidze G., Wang Q., Fu Y.; Graphene Hybrid Metasurfaces for Mid-Infrared Molecular Sensors; (2023) Nanomaterials, 13 (14), art. no. 2113; DOI: 10.3390/nano13142113. Published under the CC BY 4.0 licence.
This research was funded by the ERDF PostDoctoral Research Project No. 1.1.1.2/VIAA/4/20/740 (Towards a Universal Lab-on-Chip Sensor from a Single Graphene Sheet: from Photodetection to Biosensing), EU CAMART2 project (European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508) and Sweden’s innovation agency Vinnova (Large area CVD graphene-based sensors/IR-photodetectors 2020-00797). The APC was funded by the ERDF Project No. 1.1.1.2/VIAA/4/20/740.
Keywords: Research Subject Categories::NATURAL SCIENCES; gas sensor; graphene; metasurface; mid-infrared; photodetector